2018
DOI: 10.1615/critrevoncog.2018025946
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Radioresistance Mechanisms in Prostate Cancer

Abstract: Radiation therapy (RT) is commonly used for the treatment of localized prostate cancer (PCa). However, cancer cells often develop resistance to radiation through unknown mechanisms and pose an intractable challenge. Radiation resistance is highly unpredictable, rendering the treatment less effective in many patients and frequently causing metastasis and cancer recurrence. Understanding the molecular events that cause radioresistance in PCa will enable us to develop adjuvant treatments for enhancing the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 276 publications
(289 reference statements)
0
48
0
5
Order By: Relevance
“…Several studies have identified different molecular entities associated with radioresistance, nevertheless the underlying mechanisms are still inconclusive (16). Suggested mechanisms include hypoxia, alterations of the DNA damage response, activation of pathways involved in pro-survival or cell cycle regulation, as well as vascular, stromal, and immunological changes (1726).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified different molecular entities associated with radioresistance, nevertheless the underlying mechanisms are still inconclusive (16). Suggested mechanisms include hypoxia, alterations of the DNA damage response, activation of pathways involved in pro-survival or cell cycle regulation, as well as vascular, stromal, and immunological changes (1726).…”
Section: Introductionmentioning
confidence: 99%
“…The recurrence of cancer due to the acquisition of chemoresistance to 'classical' cytotoxic chemotherapeutics and molecularly targeted therapies [301] or radioresistance [302] remains a severe problem for the clinical treatment of cancer patients. A relatively high number of cancer patients receiving chemotherapy develop recurrent or metastatic disease due to acquiring drug resistance over time through different mechanisms, including multi-drug resistance, cell death inhibiting (apoptosis suppression), alterations in the drug metabolism, epigenetic and drug targets, enhancing DNA repair and gene amplification [303,304].…”
Section: Advancements In Vc Therapy Based On Better Profiling and Novmentioning
confidence: 99%
“…Also changes of the metabolism of cancer cells after a radiotherapy can alter the radiosensitivity of cells [13]. Still, the occurrence of radioresistance is highly unpredictable leading to less effective treatments for many patients supporting local recurrence and metastasis of prostate cancer [14]. Adjuvant therapies to further improve the efficiency of radiation therapies are urgently needed.…”
Section: Introductionmentioning
confidence: 99%